AUW TJOEI LAN SEBAGAI REPRESENTASI PERJUANGAN TRIPLE DISCRIMINATION SEJARAH PERGERAKAN NASIONAL REPUBLIK INDONESIA - Jihan Jauhar Nafisah (Jurnal Harkat : Media Komunikasi Gender, 2022)
Abstract. This article describes the ethnic Chinese as a minority who had to go through various discriminations, especially violence against women, thus giving birth to a new female figure, namely Auw Tjoei Lan during the national movement. The researcher hopes that this figure can inspire multicultural-based history learning in schools. So that students can understand that the Indonesian struggle is not only carried out by men. Many women have contributed to achieving the unity of Indonesia. In addition, the concept of women's emancipation tends to only apply to indigenous women such as Raden Ajeng Kartini and Dewi Sartika. Whereas ethnic Chinese are also part of Indonesian society and are involved in Indonesia's independence efforts. The formulation of the problem in the study of this article is "How is Auw Tjoei Lan's efforts in fighting for three discriminations in the history of the movement in Indonesia?". The process of this study uses the historical method with data sources in the study of literature. The result of this study is that Auw Tjoei Lan played a very important role during the movement in Indonesia. Auw Tjoei Lan has a high social awareness in an effort to fight for discrimination in Indonesia, especially for women. Abstrak. Artikel ini memaparkan mengenai etnis Tionghoa sebagai minoritas yang harus melalui berbagai diskriminasi khususnya kekerasan pada perempuan sehingga melahirkan seorang tokoh perempuan baru yakni bernama Auw Tjoei Lan pada masa pergerakan nasional. Peneliti berharap tokoh ini dapat menginspirasi pembelajaran sejarah berbasis multicultural di sekolah. Sehingga siswa dapat memahami bahwa perjuangan Indonesia tidak hanya dilakukan oleh kaum laki-laki. Banyak perempuan yang berjasa dalam mencapai persatuan Indonesia. Selain itu konsep emansipasi wanita cenderung hanya dinobatkan pada perempuan pribumi saja seperti Raden Ajeng Kartini, dan Dewi Sartika. Padahal etnis Tionghoa juga merupakan bagian dari masyarakat Indonesia dan ikut terlibat dalam upaya kemerdekaan Indonesia. Rumusan masalah pada kajian artikel ini adalah “Bagaimana upaya Auw Tjoei Lan dalam memperjuangkan triple discrimination pada sejarah pergerakan di Indonesia?”. Proses kajian ini menggunakan metode historis dengan sumber data secara studi literatur. Hasil dari penelitian ini adalah Auw Tjoei Lan berperan sangat penting pada masa pergerakan di Indonesia. Auw Tjoei Lan memiliki kesadaran sosial yang tinggi dalam upaya memperjuangkan diskriminasi di Indonesia khususnya bagi kalangan perempuan.